2010
DOI: 10.1111/j.1365-2184.2010.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cell proliferation and muscular structure following surgical tongue volume reduction in pigs

Abstract: Objectives-Tongue volume reduction is an adjunct treatment with several orofacial orthopedic procedures for various craniofacial deformities; it may affect structural reconstitution and functional recovery as a result of the repair process. The aim of this study was to investigate the myogenic regeneration and structural alteration of the tongue following surgical tongue volume reduction.Materials and Methods-Five 12-week-old sibling pairs of Yucatan minipigs (3 males and 2 females) were used. Midline uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…This work was supported by the grant R01 DE15659 from NIDCR. The participation of Dr. Wenmin Ye was supported by China Government Scholarship Program 2008-2010, and the participations of Mrs. Brandon Yamamura, Alfadhli Abu, and Aaron Huang were supported by the grant T32 DE007132 from NIDCR .…”
mentioning
confidence: 99%
“…This work was supported by the grant R01 DE15659 from NIDCR. The participation of Dr. Wenmin Ye was supported by China Government Scholarship Program 2008-2010, and the participations of Mrs. Brandon Yamamura, Alfadhli Abu, and Aaron Huang were supported by the grant T32 DE007132 from NIDCR .…”
mentioning
confidence: 99%
“…It is worthy to note that although there was some recovery, the restoration of the deformational capacity in the anterior part at the end of this experiment (D28–30) was still significantly smaller than that of baseline (D1). This relatively long‐term negative impact might stem from the fact that the healing after the tongue volume reduction surgery is not a process of myogenic regeneration, but fibrosis and formation of the scar tissue, as evidenced by our histological studies (Perkins et al, ; Ye et al, ). Because the performed tongue volume reduction surgery was only involved in the anterior and middle parts of the tongue (tongue blade and body), with little invasion close to the region of the two circumvallate papillae, the observed changes in tongue internal kinematics are most likely derived from the loss of the tongue mass.…”
Section: Discussionmentioning
confidence: 79%
“…It is also worthy to note that because the midline area of the tongue is made of fibrous septum, bundles of the bilateral muscle group of tongue are often approximated when the tip is reconstructed. This newly formed structure may fail to provide synchronous function as does an intact tongue (Ye et al, ). Based on all of these morphological and histological alterations, maladaptation of tongue internal kinematics may be initiated due to the natures of muscular plasticity and the consequence of motor learning, as seen in the present longitudinal observations.…”
Section: Discussionmentioning
confidence: 99%
“…In the same model, two parallel incisions of 2–3 mm depth along the length of the tongue body without tissue extirpation did not produce anatomical or functional change (Perkins, et al, 2008; Shcherbatyy, et al, 2008) (Ye, et al, 2010). In the present study the maintenance of drink measures following Ti-mag explantation indicates that observed localized tissue fibrosis and muscle fiber remodeling, including occasional divergence with normal fiber orientation, does not reach threshold for functional deficit by our measures.…”
Section: Discussionmentioning
confidence: 96%
“…Surgical removal of tongue body tissue in a mini-pig model of tongue reduction produced substantial tissue fibrosis and deficits in tongue movement (Perkins, Shcherbatyy, & Liu, 2008; Shcherbatyy, Perkins, & Liu, 2008; Ye, Abu, & Liu, 2010). In the same model, two parallel incisions of 2–3 mm depth along the length of the tongue body without tissue extirpation did not produce anatomical or functional change (Perkins, et al, 2008; Shcherbatyy, et al, 2008) (Ye, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%